2014
DOI: 10.1007/s00586-014-3378-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of basilar invagination with atlantoaxial dislocation: atlantoaxial joint distraction and fixation with transoral atlantoaxial reduction plate (TARP) without odontoidectomy

Abstract: The TARP operation and intra-operative traction could reduce the odontoid process superiorly migrating into the foramen magnum, directly ease the ventral compression of spinal cord, and fix the reduced atlantoaxial joints through a single transoral approach without the need of a posterior operation. In this stury, 21 patients were evaluated and 20 did well with TARP operation. The preliminary clinical result was satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Anterior transoral approach decompression or odontoid resection combined with posterior fixation are common techniques, but they have many drawbacks, including the deep and narrow surgical field, poor exposure of the odontoid, cerebrospinal fluid leakage, intracranial infection, high incidence of oropharyngeal dysfunction, risk of neurological deterioration, and even sudden death (23,27,31). Moreover, transoral decompression itself may also worsen atlantoaxial stability, leading to increases in translation and range of motion (ROM) in all movements except axial rotation.…”
Section: █ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior transoral approach decompression or odontoid resection combined with posterior fixation are common techniques, but they have many drawbacks, including the deep and narrow surgical field, poor exposure of the odontoid, cerebrospinal fluid leakage, intracranial infection, high incidence of oropharyngeal dysfunction, risk of neurological deterioration, and even sudden death (23,27,31). Moreover, transoral decompression itself may also worsen atlantoaxial stability, leading to increases in translation and range of motion (ROM) in all movements except axial rotation.…”
Section: █ Discussionmentioning
confidence: 99%
“…fixed dislocation), tumor, trauma, chronic inflammatory diseases (most frequently rheumatoid arthritis), and osteomyelitis (6,7,14,31). Transoral approaches can directly access the lesion site, away from laterally placed neurovascular structures (2,25).…”
mentioning
confidence: 99%
“…Transoral odontoidectomy is a high risk procedure that can lead to post-operative CSF leakage, meningitis, and death [10]. Additionally, posterior surgeries are difficult to perform on patients with C1 posterior arch deformities and congenital small pedicles [11]. Goel et al, have reported the successful employment of a direct posterior reduction without decompression in the case of fixed IAAD with os odontoideum or odontoid fracture [12].…”
mentioning
confidence: 99%
“…In 2005, a transoral atlantoaxial reduction plate, or TARP, was first used to repair basilar invagination with irreducible atlantoaxial dislocation [11]. The use of a TARP allows the relocation of the odontoid to be performed in one step without the need for a posterior operation [11]. Such a procedure could reduce complications that occur in a two-step method [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation